The Search for Life Continued Planets Around Other Stars - Jones, Barrie W. (Popular Astronomy,, 2008)
Barrie Jones addresses the question "are we alone?", which is one of the most frequently asked questions by scientists and non-scientists alike. In The Search for Life Continued, this question is addressed scientifically, and the author is not afraid to include speculation. Indeed, the author believes beyond reasonable doubt that we are not alone and this belief is based firmly on frontier science of the most imaginative kind. The author concentrates on planetary systems beyond our own but starts with life on Earth, which is the only life we know to exist, and which provides guidance on how best to search for life elsewhere. Planets are the most likely abode of life and so we start the quest with the search for planets beyond the Solar System - exoplanets. The methods of searching are outlined and the nature of hundreds of exoplanetary systems so far discovered described. In the near future we expect to discover habitable Earth-like planets. But are they actually inhabited? How could we tell? All will be revealed. This full color book is written for everybody who wants to stay in close contact with the latest on possible life on other planets.